1993
DOI: 10.1073/pnas.90.23.11074
|View full text |Cite
|
Sign up to set email alerts
|

Photolysis of a protecting group for the carboxyl function of neurotransmitters within 3 microseconds and with product quantum yield of 0.2.

Abstract: The synthesis of a photosensitive blocking group for the carboxyl function of neurotransmitters, in this case glycine, is reported. The compound, 2-methoxy-5-nitrophenyl glycine ester (caged glycine), is photolyzed by a laser pulse at 308 or 337 nm within 3 ps and with a product quantum yield of 0.2. The compound is hydrolyzed in water with a time constant i of 6.1 min at pH 7.1 and 3 hr at pH 4.0. Mouse cerebral cortical neurons containing glycine receptors were used in biological assays. A cell-flow device, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 24 publications
2
39
0
Order By: Relevance
“…A major advance has been the development of photolysable cages for soluble ligands (2). The caged ligand is allowed to slowly diffuse into tissue in its inert form, and a powerful light flash cleaves a photolabile protecting group, releasing the active ligand rapidly (within microseconds) (3,4). This provides fast on-rates that are complemented with reasonably fast off-rates, which depend on native binding affinity, diffusion, sequestration, and breakdown.…”
mentioning
confidence: 99%
“…A major advance has been the development of photolysable cages for soluble ligands (2). The caged ligand is allowed to slowly diffuse into tissue in its inert form, and a powerful light flash cleaves a photolabile protecting group, releasing the active ligand rapidly (within microseconds) (3,4). This provides fast on-rates that are complemented with reasonably fast off-rates, which depend on native binding affinity, diffusion, sequestration, and breakdown.…”
mentioning
confidence: 99%
“…Storage of stock solution did not seem to affect the ability to produce responses on uncaging, as we observed no obvious differences in response amplitudes between using fresh and stored stock solutions (fresh, 125‐160 pA; 1 day old, 100‐450 pA; 11 day old, 40‐700 pA). Finally, our recordings also indicate that BC204 is also stable at physiological pH, a basic requirement for using caged compounds in longer experiments (34). In our recordings lasting up to 1 h, we found no indication for spontaneous degradation of BC204 in ACSF at pH 7.4, allowing us to reuse BC204‐containing ACSF in another slice or to keep a slice in BC204‐containing ACSF for 2 h before starting another recording.…”
Section: Resultsmentioning
confidence: 62%
“…Hydrolysis of 1 b is dependent upon pH. As expected [20] the compound is more stable at lower pH. We found that 17 % of 1 b was hydrolysed in citrate/phosphate buffer at pH 4.0 within 24 h. Because hydrolysis in the dark is often a serious problem it seems that 1 b is less suitable as caged compound and requires some care to minimize contamination by free amino acid.…”
Section: Resultsmentioning
confidence: 69%